2016
DOI: 10.4028/www.scientific.net/kem.723.56
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modifying Agents on the Mechanical Properties of Straw Flour/Waste Plastic Composite Materials

Abstract: Though there has been a large number of studies concerning the modification of wood plastic composite materials, there is still more to be done. This report aims to study the effect of the coupling agents (PP-g-MAH, silane, titanate) and compatibilizer(SBS) on the mechanical properties of straw flour/waste plastic composites. Straw flour, waste plastic, modifying agents and other additives were mixed evenly in a high speed mixing machine. And the mixed materials were compounded into the pelllets using the twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…As for composite materials, the coupling agent acts as a molecular bridge that not only plays a coupling role, but also influences its performance in various aspects 36–40 . Therefore, the electrical properties of both films were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…As for composite materials, the coupling agent acts as a molecular bridge that not only plays a coupling role, but also influences its performance in various aspects 36–40 . Therefore, the electrical properties of both films were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Panels made using a mixture of macadamia shells and automotive PW have exhibited more strength and resistance to fire than panels made entirely of automotive PW [77]. Similarly, it was discovered that when PW was combined with straw flour, its mechanical characteristics greatly improved [78]. It was also reported that the field of PW and woody biomass composites is still in its initial stages and needs additional investigations before its long-term viability can be determined.…”
Section: Recyclingmentioning
confidence: 99%
“…Residual film and straw are the main components of mechanically recovered waste and have a wide range of applications. Film is the main component that can be recycled for granulation [20,21]; straw is the second main component that can be used to adjust the carbon-nitrogen ratio of compost and to produce animal feed [22,23]; the waste mixture of the two can be used to produce composite panels for the construction and decoration industries [24][25][26]. However, all of the above resource recovery methods require that the mixed material is first shredded, particularly the knotted feature, to ensure that the subsequent process can be carried out smoothly.…”
Section: Introductionmentioning
confidence: 99%